ANALISIS KESULITAN SISWA MENYELESAIKAN SOAL CERITA MATERI PROGRAM LINEAR BERDASARKAN GAYA BELAJAR SISWA SMA - Isma Nuriza; Edy Yusmin; Bistari Bistari (Universitas Tanjungpura, 2020)
Abstract This is a qualitative research with descriptive method in purpose to acknowledge students' difficulty in solving word problems of linear program. The main aspect that will be explained in this research is the students' difficulty in solving linear program related problems based on students' learning style of eleventh grade in SMA Negeri 1 Sungai Raya. The research subjects were six eleventh grade students in the class of XI IPS 4 to which they have different learning styles: visual, auditory, and kinestetic. The result showed that students with those three learning styles experienced difficulties in the stage of understanding the problem, creating mathematics model and executing the algorithm (steps). Beside that, there were some factors that affected students difficulty in solving the word problems of linear program: students didn't understandenough to this learning subject, students weren't seemingly thorough in study, the presenting of material was still not categorized as good, lacking of learning medias and the fact that students were easily disturbed by their classmates during the learning process. Keywords: Difficulty, Learning Style, Linear Program, Word Problem